Determination of Reservoirs of Cutaneous Leishmaniasis by PCR Molecular Method in the Villages of Central County of Qom Province - Abedin Saghafipour; Yavar Rassi; Mohammad-Reza Abai; Mohammad-Ali Oshaghi; Babak Farzinnia; Reza Mostafavi; Mahdi Noroozi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2013)
Background and Objectives: Cutaneous leishmaniasis is a major health problem in many parts of Iran and its main foci are in various parts of the country. This study was carried out with the intention of examining the species composition of the possible disease reservoirs in the cutaneous leishmaniasis focus in the selected villages of central county of Qom province.   Methods: Study was done as a descriptive, cross-sectional study on rodents (possible leishmaniasis reservoirs) in the selected rural areas of Qomrood and Ghanavat located in central parts of Qom province in 2010. In this research, a total of 46 small rodents were hunted by live traps from 5 selected villages. A Smear prepared from auricle or suspicious lesions on skin, and after Giemsa staining, the smears were examined for the presence of leishman’s bodies. After extracting DNA from positive smears, PCR technique was exploited to determine the parasite species.   Results: A total 46 small mammals were hunted and identified by the authentic keys. They included 31 rodents (67.4%) were Meriones libycus , 8 (17.4%) Allactaga elater , 4 (8.7%) Mus musculus , 2 (4.3%) Nesokia indica and one (2.7%) Hemiechinus auritus . The results of PCR demonstrated that 3.7% of M. libycus rodents were infected by Leishmania major.   Conclusion: The results of this study showed that epidemic cutaneous leishmaniasis in the central county of Qom province was zoonotic and its reservoir was species of rodents. Therefore, determining disease type and its reservoir can help health care authorities to adopt appropriate strategies for prevention and control of the disease in this area.